2017
DOI: 10.1111/apa.13816
|View full text |Cite
|
Sign up to set email alerts
|

Observation method identifies that a lack of canonical babbling can indicate future speech and language problems

Abstract: Aim: We investigated how accurate observations of canonical babbling (CB) were and explored predictive babbling measures in children with and without medical diagnoses of conditions that can lead to speech and language problems.Methods: From 2012 to 2014 this Stockholm-based study recruited 38 children aged nine months to 21 months with medical diagnoses and 30 children aged 10 months without diagnoses and included 21 previously studied 12-month-old children without medical diagnoses. CB and consonant sound pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 24 publications
(49 reference statements)
2
34
1
Order By: Relevance
“…The core problem that causes late babbling could generalize to other aspects of language and literacy development. Thus, the absence of canonical babbling and persistence of precanonical vocalizations as the predominant vocalization pattern beyond 10-12 months of age may indicate atypical vocal development and precede later speech and language deviations [25,39]. Indeed, Oller et al reported that infants who did not produce canonical syllables at 10-12 months also had a reduced expressive vocabulary at 18, 24, and 30 months of age [24].…”
Section: Introductionmentioning
confidence: 99%
“…The core problem that causes late babbling could generalize to other aspects of language and literacy development. Thus, the absence of canonical babbling and persistence of precanonical vocalizations as the predominant vocalization pattern beyond 10-12 months of age may indicate atypical vocal development and precede later speech and language deviations [25,39]. Indeed, Oller et al reported that infants who did not produce canonical syllables at 10-12 months also had a reduced expressive vocabulary at 18, 24, and 30 months of age [24].…”
Section: Introductionmentioning
confidence: 99%
“…This observational study by Lohmander et al. showed that a lack of canonical babbling in children between nine and 21 months can indicate future speech and language problems.
…”
Section: Lack Of Babbling May Indicate Future Speech Problemsmentioning
confidence: 94%
“…Previously validated variables (i.e. occurrence of CB, oral stops, anterior placement and specifically dental/alveolar placement, and total number of different consonants) were used to evaluate babbling by standardised observation [29]. [30].…”
Section: Methodsmentioning
confidence: 99%
“…The observation method was used for assessment of babbling [29]. The parent was told to play and communicate with the child Parents received instructions to play and talk, as they would do at home during 30-40 min.…”
Section: Observation Of Babblingmentioning
confidence: 99%